2015
DOI: 10.1007/s00432-015-2011-5
|View full text |Cite
|
Sign up to set email alerts
|

CITED4 gene silencing in colorectal cancer cells modulates adherens/tight junction gene expression and reduces cell proliferation

Abstract: PurposeCITED4 is one member of a family of transcriptional cofactors, several of which are deregulated in a variety of tumors, including colorectal cancer (CRC). We modulated CITED4 expression, in vitro, and analyzed the associated phenotypic and gene expression changes.MethodsCITED4-overexpressing and shRNA-mediated knockdown cell lines and control cell lines were established in the CRC cell line SW480. The cells were analyzed for changes in proliferation, apoptosis/cell cycle, migration, invasion, colony for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
0
24
1
Order By: Relevance
“…CITED4 interacts with CBP/p300, as well as the transcription factor AP‐2 (TFAP2), mediating TFAP2‐dependent transcription . Notably, CITED4 is downregulated in several cancer types, including colorectal cancer, brain cancer, and breast cancer, and contributes to the acquisition of malignant characteristics such as proliferation, survival, angiogenesis, and adherens junctions/tight junctions . Furthermore, Fox et al showed that the expression of CITED4 can be downregulated or translocated to the cytoplasm in breast cancer and inhibits HIF‐1α‐mediated transcription and angiogenesis through direct competition of p300 binding.…”
Section: Discussionmentioning
confidence: 99%
“…CITED4 interacts with CBP/p300, as well as the transcription factor AP‐2 (TFAP2), mediating TFAP2‐dependent transcription . Notably, CITED4 is downregulated in several cancer types, including colorectal cancer, brain cancer, and breast cancer, and contributes to the acquisition of malignant characteristics such as proliferation, survival, angiogenesis, and adherens junctions/tight junctions . Furthermore, Fox et al showed that the expression of CITED4 can be downregulated or translocated to the cytoplasm in breast cancer and inhibits HIF‐1α‐mediated transcription and angiogenesis through direct competition of p300 binding.…”
Section: Discussionmentioning
confidence: 99%
“…The genes of interest were normalized against the housekeeping genes DCTN2 and PGK1. For a detailed protocol, see Rogers et al [18].…”
Section: Microarray Candidate Gene Validation By Qrt-pcrmentioning
confidence: 99%
“…The protein of interest was identified using Enhanced Chemiluminescence (ECL, Pierce) coupled with X-ray film exposure. For a detailed protocol, see Rogers et al [18].…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have now pointed out the expression and the role of CITED proteins in stem cells (including ESC), in which they are involved in selfrenewal and cell fate decisions [38,[41][42][43][44][45][46]. Not surprisingly, due to the plethora of cellular and embryonic functions exerted by CITED1, CITED2 and CITED4, these genes were also showed to play intricate roles in tumorigenic processes [5,45,[47][48][49][50][51][52][53][54][55][56][57][58][59]. Therefore, CITED proteins are truly Regenerative Medicine Frontiers…”
Section: Introductionmentioning
confidence: 99%